Mental health of medical students during the COVID19: Impact of studies years - Aziz Essadek; Florence Gressier; Marion Robin; Gérard Shadili; Lise Bastien; Jean-Christophe Peronnet; Bruno Falissard; Thomas Rabeyron (Journal of Affective Disorders Reports, 2022)
Background: The COVID-19 pandemic had led to severe education disruption in many countries, including for medical students (MS). We aimed to evaluate MS mental health in France and search for a difference depending on studies’ years and clinical activities. Methods: In a cross-sectional, survey-based study during the first confinement, 668 (8.35%) MS were compared to 7 336 non-medical students (non-MS) (91.65%). The PHQ-9 (≥ 10), the GAD-7 (≥ 8), and the IES-R (≥ 26) were collected to assess depressive, anxiety, and distress symptoms. Multivariable logistic regression analyses were performed. Results: MS reported significant psychological distress (depressive symptoms: 38.17%, anxiety: 38.77% and distress: 36.83%). Compared to non-MS, they reported less significant depressive (OR, 0.80; 95% CI, 0.67–0.91; P = .007) and distress symptoms (OR, 0.73; 95% CI, 0.62–0.87; P < .001), after taking into account potential confounding variables including COVID-19 diagnosis. First year-MS reported higher rates of significant psychological distress than MS with clinical activities. Moreover, depressive symptoms’ rates were higher among MS with COVID-19 diagnosis (OR, 2.61; 95% CI, 1.21–6.13; P = .016). Conclusions: Special attention should be offered to first year-MS and MS with COVID-19 diagnosis. Systematic companionship could be implemented for first year MS, and systematic psychiatric/psychological consultations for students with COVID-19 diagnosis.